2016
DOI: 10.4103/0974-9233.171780
|View full text |Cite
|
Sign up to set email alerts
|

Preferred method of education among patients in ophthalmic care in Saudi Arabia

Abstract: Purpose:Educating patients about their diagnosis and proposed management is integral part of healthcare. Often patient noncompliance is due to a lack of knowledge that could result in irreversible ocular damage. In an era where access to information is virtually unlimited, an understanding of the preferred method of eye care education among patients is required for greater effectiveness in lowering morbidity and mortality of diseases.Subjects and Methods:Patients visiting the ophthalmology clinics of a tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…[26] Studies have demonstrated the patient preference and effectiveness of mobile-based health applications in improving health awareness in different studies in Saudi Arabia. [272829]…”
Section: Discussionmentioning
confidence: 99%
“…[26] Studies have demonstrated the patient preference and effectiveness of mobile-based health applications in improving health awareness in different studies in Saudi Arabia. [272829]…”
Section: Discussionmentioning
confidence: 99%
“…Saudi glaucoma patients require information on a range of domains such as definition of glaucoma, possible risk factors, pathophysiology, effect on vision, and treatment. According to a report published by AlHilali et al, 20 obtaining information from an eye care provider is the preferred method listed by the majority of patients attending ophthalmic care in Saudi Arabia. This places an additional burden on treating ophthalmologists to bridge this gap in knowledge, a task that could be difficult to fulfill given a busy clinical practice and the overall shortage of local ophthalmologists with subspecialty training in glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…The information given to the patient about his disease has a crucial impact on the process of understanding his clinical condition and prognosis. This is often essential for effective adherence to treatment, so patient-centered education is one of the pillars of medical intervention, thus some apps are developed to deepen patient's knowledge about his disease 40 .…”
Section: Community Patient Education and Assistancementioning
confidence: 99%
“…A study carried out in Saudi Arabia showed that although individual and group sessions were the main source of information about pathological conditions in ophthalmology; however mobile applications already represented a viable alternative to develop this knowledge, which can facilitate patient follow-up 40 .…”
Section: Community Patient Education and Assistancementioning
confidence: 99%